“Where Butchers Sing Like Angels,” Of Captive Bodies and Colonized Minds (With a Little Help from Louise Erdrich) - Poks, Małgorzata (Review of International American Studies, 2020)
The Master Butchers Signing Club – Louise Erdrich’s “countehistory” (Natalie Eppelsheimer) of the declared and undeclared wars of Western patriarchy–depicts a world where butchering, when done with precision and expertise, approximates art. Fidelis Waldvogel, whose name means literally Faithful Forestbird, is a sensitive German boy turned the first-rate sniper in the First World War and master butcher in his adult life in America. When Fidelis revisits his homeland after the slaughter of World War II, Delphine, his second wife, has a vision of smoke and ashes bursting out of the mouths of the master butchers singing onstage in a masterful harmony of voices. Why it is only Delphine, an outsider in the Western world, that can see the crematorium-like reality overimposed on the bucolic scenery of a small German town? Drawing on decolonial and Critical Animal Studies, this article tries to demystify some of the norms and normativities we live by.